MİHNE SÜRECİNDE BİR EHLİ HADİS, MUHAMMED BİN İSMAİL EL-BUHÂRİ VE HALKU EF’ÂLİ’L-İBÂD ADLI ESERİ - Temiz, Rabia Zahide (Fırat University, 2015)
Hicrî 2. asrın son çeyreği ve 3. asrın ilk yarısı, İslâm düşüncesinin gelişiminde şüphesiz en önemli paya sahip olan dönemdir. “Mihne” olarak adlandırılan ve siyâsî idarenin de dâhil olduğu, hatta bizzat faili olduğu sorgulama sürecinde, Sünnet ve hadis taraftarları Kur'ân'ın mahlûk olduğu görüşünü kabul etmeye zorlanmışlardır. Buhârî de tartışmalarda taraf haline getirilmiş, Lafziyye görüşüne sahip olduğu iddiasıyla Buhârâ?dan sürgün edilmiştir. Bu makale, Buhârî?nin tartışmalarla doğrudan alakalı olarak kaleme aldığı Halku ef?âli?l ibâd adlı eserini hadis ilmi açısından incelemeyi ve Buhârî özelinde ehl-i hadis?in mihne karşısındaki duruşunu tahlil etmeyi amaçlamaktadır

The last quarter of the second century AH and the first half of the third century AH was undoubtedly the most important era in the development of Islamic thought. In the questioning process called as "Mihna", in which the political administrators were involved and even sometimes the perpetrators, adherents of sunnah and hadith were forced to accept the notion that the Qur'an was created. Bukhari, one of the leading names of ahl al-hadith has been forced to express his opinion in the debate by some and he has been exiled from Bukhara by claiming to have Lafziyye opinion. This article aims to analyse the work “Khalq af?aal al-ibaad” which was penned by him as directly relevant to the discussion of hadiths and to assay ahl al-Hadith?s attitude, especially that of Bukhari?s, during the minha
One of The Hadith Advocator in the Mihna Process, Muhammad Ibn Ismail Al-Bukhari and His Writen Book Khalq Af'aal Al-Ibaad